2014
DOI: 10.1007/s00436-014-3886-9
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of calculation methods used for the determination of anthelmintic resistance in sheep in a temperate continental climate

Abstract: This study compared results obtained with five different fecal egg count reduction (FECR) calculation methods for defining resistance to ivermectin, fenbendazole, and levamisole in gastrointestinal nematodes of sheep in a temperate continental climate: FECR1 and FECR2 used pre- and posttreatment fecal egg count (FEC) means from both treated and control animals, but FECR1 used arithmetic means, whereas FECR2 used geometric means; FECR3 used arithmetic means for pre- and posttreatment FECs from treated animals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…The only differences amongst the equations were minor re-rankings that affected which treatment differed from LEV for relative efficacy. Some studies have found different results for resistance based on equation (Falzon et al, 2014;Pena-Espinosa et al, 2014). This was suggested to be because of a lower level of resistance to the anthelmintics tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only differences amongst the equations were minor re-rankings that affected which treatment differed from LEV for relative efficacy. Some studies have found different results for resistance based on equation (Falzon et al, 2014;Pena-Espinosa et al, 2014). This was suggested to be because of a lower level of resistance to the anthelmintics tested.…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested to be because of a lower level of resistance to the anthelmintics tested. The equation that is the most accurate for determining anthelmntic resistance remains undetermined and is an area of investigation (Calvete and Uriarte, 2013;McKenna, 2013McKenna, , 2014Falzon et al, 2014;Pena-Espinosa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data validation and cleaning were performed by using Microsoft Excel 2013. Calculation of faecal egg count reduction (FECR) was performed using the contributed R package “e ggsCount ” [ 23 ] and following the WAAVP guidelines [ 19 , 24 ]. FECR (%) was calculated between treatment and control group at post-treatment collection for each anthelmintic.…”
Section: Methodsmentioning
confidence: 99%
“…En las experiencias A y B, la clasificación taxonómica de las larvas obtenidas en los coprocultivos pretratamiento indicó la presencia casi exclusiva de Haemonchus contortus (98%) y el resto perteneciente al género Trichostrongylus spp., mientras que en la experiencia C la participación relativa de estos géneros fue de 78 % y 22 %, respectivamente. Debido a que existen algunas evidencias conflictivas sobre que fórmula utilizar para determinar la eficacia de los antihelmínticos cuando se utiliza el TRCH (Falzon et al, 2015), en la presente experiencia y para asegurar la interpretación de los resultados se utilizaron tres fórmulas distintas, no observándose diferencias significativas entre las mismas. Los tratamientos resultaron en reducciones del hpg utilizando las diferentes fórmulas que variaron entre el 99,7% y100% para las tres experiencias.…”
Section: )unclassified